Independent component regression applied to genomic selection for carcass traits in pigs - Azevedo, Camila Ferreira; Resende, Marcos Deon Vilela de; Silva, Fabyano Fonseca e; Lopes, Paulo Sávio; Guimarães, Simone Eliza Facioni (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the efficiency of the independent component regression (ICR) method for the estimation of genomic values and of SNP marker effects for carcass traits in a F2 pig population (Piau x commercial line). The methods were evaluated by the agreement between the genetic predicted values and the corrected phenotypes observed by cross‑validation, and they were also compared with other methods generally used for the same purposes, such as RR‑BLUP, PCR, and PLS. The ICR and PCR methods show similar results, but ICR has the highest accuracy prediction values.
Keywords: Sus scrofa; BLUP; SNP markers; random regression; dimensional reduction